The sensory profile of children with speech and language disorders in London and the south of England - Van der Linde, Janine (My University, 2009)
Children presenting with communication difficulties are among the most commonly occurring developmental problems. They were observed to have problems with their everyday activities in all the occupational performance areas, as well as displaying behaviours that have a negative impact on their functioning. These behaviours appear similar to those described in children with sensory processing and sensory modulation difficulties. Literature indicated a possible connection between speech and language difficulties and poor sensory integration. This study used the Sensory Profile, a parent report measurement of the child’s sensory responsiveness in daily life, to investigate the sensory processing and modulation of children with Specific Language Impairment, as reflected in their behavioural and emotional responses. The study indicated that this population has specific areas of sensory processing that are unique to children with SLI and that differ significantly in their sensory responsiveness from typical children and children with other conditions like Autism and Attention Deficit Hyperactivity Disorder.
Keywords: children; London; speech disorders; language disorders